The Decline of Basic Ophthalmology in General Medical Education: A Scoping Review and Recommended Potential Solutions - Jennifer Liao; Robin Redmon Wright; Gargi K Vora (Journal of Medical Education and Curricular Development, 2024)
OBJECTIVE This literature review aims to explore research and conceptual pieces on the state of ophthalmology education and suggest potential ways to address current challenges. METHODS A search was conducted in PubMed, ERIC, Web of Science, and Google Scholar with combinations of the following search terms: “ophthalmology education,” “undergraduate medical education,” “medical student,” “United States,” and “Canada.” Eliminating irrelevant articles yielded 47 articles. Three were excluded because of region and focus, leaving 44. After examining the citations, we generated an additional 22 texts for review, totaling 66 articles. RESULTS Four primary themes were identified: (1) challenges to ophthalmological education in the U.S. and Canada, (2) potential remedies for optimizing ophthalmology curriculum, (3) technology in ophthalmology education, and (4) innovative ophthalmology teaching approaches. Major challenges included the lack of a standardized curriculum and inadequate clinical exposure and skills training. A number of remedies were proposed, such as standardizing curriculum and furthering faculty involvement, utilizing technology as time-effective learning aids, and employing innovative teaching approaches such as service learning. CONCLUSION In light of challenges in ophthalmology education, curriculum designers should consider Cognitive Load Theory (CLT) to assist students to remember meaningful exposures to ophthalmology knowledge and techniques. Based on CLT, we suggest two potential approaches to incorporating ophthalmology curriculum. The first is to embrace interdisciplinary collaborations and place ophthalmology knowledge in varied contexts to facilitate schema construction. The second is to incorporate ophthalmology diagnostics requirements into OSCEs and utilize simulation models for students to gradually increase the fidelity of tasks and devote cognitive resources fully to learning.